Clinical significance of serum YKL‐40 in Behçet disease. (23rd March 2016) - Seo, J.; Ahn, Y.; Zheng, Z.; Kim, B.O.; Choi, M.J.; Bang, D.; Kim, D.Y.
Summary: Background: Serum YKL‐40 is an inflammatory biomarker of endothelial dysfunction and may play a role in the inflammatory process of Behçet disease (BD). Objectives: Serum YKL‐40 levels were evaluated in patients with BD in order to identify associations with other inflammatory cytokines and establish laboratory parameters. Serum YKL‐40 levels were also compared with BD clinical features and disease activity. Methods: In total, 112 patients with BD and 45 age‐ and sex‐matched healthy volunteers were included. Disease activity was assessed with BD Current Activity Form score and Electronic Medical Record‐based Activity Index (EMRAI) score. Results: Serum YKL‐40 levels were significantly higher in patients with BD (median 41·88, range 12·52–171·30 ng mL −1 ) than in healthy volunteers (median 20·92, range 5·01–64·20 ng mL −1 ; P < 0·01). The cut‐off value for YKL‐40 (30·005 ng mL −1 ) was determined from the receiver operating characteristic curve. EMRAI scores and the proportion of patients in the active phase of BD presenting with two or more major criteria were significantly higher in patients with elevated YKL‐40 levels ( P = 0·04 and P = 0·04, respectively). A statistically significant elevation in YKL‐40 levels was observed in patients with active BD compared with patients with inactive BD ( P = 0·05). Serum YKL‐40 values were positively correlated with interleukin‐6 and EMRAI scores (both P = 0·04), indicating that serum YKL‐40 levels are increased in patients with BD and positively correlate with disease activity. Conclusions: YKL‐40 may play a role in the pathophysiology of BD and provide a useful marker for monitoring patients with BD. Abstract : What's already known about this topic? YKL‐40, secreted by activated macrophages and neutrophils, is a potential biomarker of inflammation and endothelial dysfunction. Behçet disease (BD) is a chronic multisystemic inflammatory disease, characterized by neutrophil hyperactivation and endothelial injury with subsequent dysfunction. What does this study add? Serum YKL‐40 levels are increased in patients with BD and positively correlate with disease activity. YKL‐40 may play a role in the pathophysiology of BD and could provide a useful marker for monitoring patients with BD.